Synthesis of Aminotroponyl‐/Difluoroboronyl Aminotroponyl Deoxyuridine Phosphoramidites. Issue 12 (21st December 2022) - Palai, Bibhuti Bhusana; Panda, Subhashree S.; Sharma, Nagendra K.
Abstract: This report describes the chemical synthesis of aminotroponyl‐conjugated deoxyuridine analog ( at ‐dU ) and its difluoroboron complex ( dfbat‐ dU ) and their phosphoramidites by using the versatile phosphorylating reagent 2‐Cyanoethyl N, N ‐diisopropylchlorophosphoramidite. Tropolone is a non‐benzenoid aromatic bioactive natural fluorescent molecule, possessing intramolecular charge transfer and metal chelating properties with transition metal ions such as Cu 2+/ Zn 2+/ Ni 2+ . Its synthetic derivatives, 2‐aminotropones also exhibit unique bioactivities and are considered potential therapeutic drug candidate. Recently, the fluorescence properties of aminotropone has improved by complexing with difluoroboron residue that generates aminotroponyl‐BODIPY analog. These could be employed for the synthesis of at ‐dU/ dfbat‐ dU containing DNA oligonucleotides for designing the 11 B/ 19 F‐NMR/fluorescence‐based DNA probes. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Synthesis of N ‐propargyl‐2‐aminotropone (2 ) and difluoroboronyl N ‐propargyl‐2‐aminotropone (3 ) molecules. Basic Protocol 2 : Synthesis of N ‐propargyl‐2‐aminotroponyl deoxyuridinyl ( at ‐dU ) phosphoramidites (7 ). Basic Protocol 3 : Synthesis of difluoroboronyl N ‐propargyl‐2‐aminotroponyl deoxyuridinyl ( dfbat ‐dU ) phosphoramidites (10 )